Kemampuan Literasi Sains Siswa melalui Model Argument Driven Inquiry berbasis Blended Learning - Dinda Agustina Rismaya Citra; Ilah Nurlaelah; Ina Setiawati (Journal of Natural Sciences, 2023)
The demands of students in the 21st century are one of them being able to communicate effectively. In order to achieve these demands students must have scientific literacy skills. The ADI model is designed to help students understand how to make scientific explanations, generalize scientific facts, use data to answer scientific questions and reflect on the work they have done. The ADI model syntax can facilitate scientific literacy skills. This study aims to determine the effect of the ADI model based on blended learning on the scientific literacy abilities of SMA Negeri 1 Kuningan students and to determine student responses to the ADI model and blended learning. This study was designed using the Pretest – Posttest Control Group design. The population of this study were all students of class XI MIPA at SMA Negeri 1 Kuningan for the 2020/2021 academic year. Sampling using purposive sampling technique. Data collection with description tests, questionnaires and documentation. The results of the hypothesis test showed that the application of the ADI model using the t test obtained 2.61 1.98 meaning that the application of the Blended Learning-based Argument Driven Inquiry (ADI) learning model could affect students' scientific literacy skills on the concept of the Dangers of Cigarettes in class XI MIPA SMA Negeri 1 Kuningan supported by questionnaire data shows a response agreeing that students' scientific literacy skills can be facilitated by applying the ADI model based on Blended Learning.